2016
DOI: 10.1097/mao.0000000000001017
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Histopathologic Findings in Patients With Systemic Lupus Erythematosus

Abstract: Hypothesis We hypothesized that, in archived human temporal bone samples from patients with systemic lupus erythematosus (SLE), a pathologic condition exists in the stria vascularis and cochlear hair cells. Background Sensorineural hearing loss is a common feature in SLE patients. However, the pathophysiologic mechanism of cochlear dysfunction is unclear. Methods We examined 15 temporal bone samples from 8 SLE patients, along with 17 samples from 10 age-matched healthy control patients. The samples were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Kariya et al . examined 15 temporal bone samples from 8 systemic lupus erythematosus patients, along with 17 samples from 10 age-matched healthy control patients 24 . They found a positive correlation between the loss of cochlear hair cells and the duration of systemic lupus erythematosus, and concluded that it represented the histopathological basis for the cochlear dysfunction, including SNHL, experienced by systemic lupus erythematosus patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kariya et al . examined 15 temporal bone samples from 8 systemic lupus erythematosus patients, along with 17 samples from 10 age-matched healthy control patients 24 . They found a positive correlation between the loss of cochlear hair cells and the duration of systemic lupus erythematosus, and concluded that it represented the histopathological basis for the cochlear dysfunction, including SNHL, experienced by systemic lupus erythematosus patients.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Vasculitis appears to be the major factor involved in cochlear and vestibular damage. 2 , 12 , 13 , 25 , 36 , 37 …”
Section: Pathophysiology Of Inner Ear Involvement In Slementioning
confidence: 99%
“…33 Atrophy of the stria vascularis and loss of spiral ganglion cells are observed in systemic lupus erythematous. [34][35][36] These inflammatory processes result in fibrosis and osteoneogenesis [37][38][39] and retrograde neuronal degeneration. 26…”
Section: Histopathologymentioning
confidence: 99%
“…Basement membrane Immunoglobulin G deposition and loss of spiral ganglion neurons have been observed in Sjögren's . Atrophy of the stria vascularis and loss of spiral ganglion cells are observed in systemic lupus erythematous . These inflammatory processes result in fibrosis and osteoneogenesis and retrograde neuronal degeneration …”
Section: Histopathologymentioning
confidence: 99%